Effects of latitude and depth on the beta diversity of New Zealand fish communities. - Zintzen V; Anderson MJ; Roberts CD; Harvey ES; Stewart AL (Massey University)
Marine ecosystems are difficult to sample quantitatively at increasing depth. Hence, few studies attempt to measure patterns of beta diversity for ecological communities in the deep sea. Here we (i) present and quantify large-scale gradients in fish community structure along depth and latitude gradients of the New Zealand EEZ, (ii) obtain rigorous quantitative estimates of these depth (50-1200 m) and latitudinal effects (29.15-50.91°S) and their interaction, and (iii) explicitly model how latitudinal beta diversity of fishes varies with depth. The sampling design was highly structured, replicated and stratified for latitude and depth, using data obtained from 345 standardised baited remote underwater stereo-video deployments. Results showed that gradients in fish community structure along depth and latitude were strong and interactive in New Zealand waters; latitudinal variation in fish communities progressively decreased with depth following an exponential decay (r 2 = 0.96), revealing increasingly similar fish communities with increasing depth. In contrast, variation in fish community structure along the depth gradient was of a similar magnitude across all of the latitudes investigated here. We conclude that an exponential decay in beta diversity vs depth exists for fish communities present in areas shallower than the New Zealand upper continental slope.